The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4322/2526-8910.ctoao1821
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de gestores acerca da atuação e inserção de terapeutas ocupacionais na atenção básica à saúde

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Resumo: Introdução: A terapia ocupacional é uma profissão da área de saúde que tem interfaces na educação e no campo social, cujas ações objetivam a participação dos indivíduos em ocupações cotidianas que promovem a construção de sua identidade, saúde e bem-estar. Sendo assim, o t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Os termos mais citados pelos gestores ao se referirem à profissão foram "cotidiano", "atividades" e "ocupação", tendo sido mencionado, também, que a profissão se volta para as atividades diárias do sujeito e realiza adaptações de utensílios. No entanto, verificou-se que eles confundem práticas e atribuições da terapia ocupacional com as da fisioterapia, o que aponta, também, para seu desconhecimento acerca da especificidade da profissão (Miranda et al, 2019).…”
Section: Discussionunclassified
“…Os termos mais citados pelos gestores ao se referirem à profissão foram "cotidiano", "atividades" e "ocupação", tendo sido mencionado, também, que a profissão se volta para as atividades diárias do sujeito e realiza adaptações de utensílios. No entanto, verificou-se que eles confundem práticas e atribuições da terapia ocupacional com as da fisioterapia, o que aponta, também, para seu desconhecimento acerca da especificidade da profissão (Miranda et al, 2019).…”
Section: Discussionunclassified
“…The terms most cited by managers, highlighting occupational therapy professional, were: "everyday life", "activities" and "occupation", and it was also mentioned that the profession focuses on the subject's daily activities and adapts utensils. However, it was found that they confuse practices and attributions of occupational therapy with those of physiotherapy, which also points to their lack of knowledge about the specificity of the profession (Miranda et al, 2019). Some research participants brought, in their reports, the experience of being confused with recreators and/or workshops, which also demonstrates the insufficient understanding of the management, of the users of the services and their families about the principles and practices that constitute the performance of the occupational therapy in the field of mental health.…”
Section: Discussionmentioning
confidence: 99%